Development and validation of atomic absorption spectrometry for the determination of zink and mercury analyzer for determination of Mercury in cream cosmetics - Rohman, Abdul; Wijayanti, Erni (Journal of Food and Pharmaceutical Sciences, 2015)
An atomic absorption spectrometry for the quantification of zink (Zn) and mercury analyzer  for the quantification of mercury (Hg) levels in cream cosmetic were developed and validated. The method was validated for linearity and range, precision, accuracy, limit of detection (LOD) and limit of quantification (LOQ). The standard curves were linear over the concentration of 0.1-1.2 µg/mL (Zn) and 0.05-2.0 µg/L (Hg) with coefficient of correlation (r) > 0.99. The detection limits obtained were 2.8614 µg/g sample (Zn) and 0.4749 ng/g sample. The quantification limit  obtained were 9.5281 µg/g sample (Zn) and 1.5827 ng/g sample. The relative standar deviation (RSD) values found to be 8.67 % for its intraday precision and 9.89 % for its interday precision (Zn) and 12.69 % for its intraday precision and 7.17 % for its interday precision (Hg). These RSD values are lower than those required by RSD Horwitz unction. The mean recovery percentage was 94.28 % (for Zn) and 78.65% (for Hg). These developed methods were succesfully used for determination of Zn and Hg in cream cosmetics products. Key words: mercury, zink, atomic absorption spectroscopy, mercury analyzer, cream cosmetic